2020
DOI: 10.3390/app10082876
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality Assessment of Digital Image Capturing Devices for Melanoma Detection

Abstract: The fast-growing incidence of skin cancer, especially melanoma, is the guiding principle for intense development of various digital image-capturing devices providing easier recognition of melanoma by dermatologists. Handheld and digital dermoscopy, following of mole changes with smartphones and digital analysing of mole images, is based on evaluation of the colours, shape and deep structures in the skin moles. Incorrect colour information of an image, under- or overexposed images, lack of sharpness and low res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…Store-and-forward TD relies on the transmission and storage of photos, and a review written during COVID-19 showed that smartphones are a widespread method of taking clinical photos [ 54 ]. Another 2020 study revealed that smartphones with automatic camera settings produce oversaturated photos, making it difficult to determine possible malignancy based on color of lesions [ 55 ]. In addition to the implied risk of misdiagnosis, taking and storing photos on personal smartphones is not considered a secure way of storing patient information and can lead to Health Insurance Portability and Accountability Act (HIPAA) violations [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Store-and-forward TD relies on the transmission and storage of photos, and a review written during COVID-19 showed that smartphones are a widespread method of taking clinical photos [ 54 ]. Another 2020 study revealed that smartphones with automatic camera settings produce oversaturated photos, making it difficult to determine possible malignancy based on color of lesions [ 55 ]. In addition to the implied risk of misdiagnosis, taking and storing photos on personal smartphones is not considered a secure way of storing patient information and can lead to Health Insurance Portability and Accountability Act (HIPAA) violations [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Visual signals (digital images or videos) undergo a wide variety of distortions during acquisition, compression, transmission, and storage. Thus, image quality assessment (IQA) is crucial to predict the quality of digital images in many applications, such as compression, communication, printing, display, analysis, registration, restoration, and enhancement [ 1 , 2 , 3 , 4 ]. Generally, it can be used in benchmarking any image processing algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable interest in the use of smartphone applications to facilitate computer-aided diagnosis and monitoring of suspicious skin lesions, although the results generated by the software have so far not been shown to be of clinical utility ( Freeman et al., 2020 ; Matin and Dinnes, 2021 ). A recent study showed that the parameters of commercial digital cameras and smartphones could be modified to increase the accuracy of the images, generally by disabling some automatic settings that were intended to produce more visually appealing images for consumers but can reduce accuracy ( Dugonik et al., 2020 ). For optimal results with DermaViz analysis of smartphone images, it will be important to specify acquisition protocols to promote accuracy and consistency between images acquired over time.…”
Section: Discussionmentioning
confidence: 99%